Plant-based Exosome Injections for Skin Wound Healing: Experimental Study - Noury Adel, MSc, DHM; Nenad Stankovic, DDS; Gerardo Cervantes, MD; Amira Gindi, RNP; Lamiaa Mohamed Shawky, PHD (Plastic and Reconstructive Surgery, Global Open)
Background:. This study aimed to evaluate the impact of plant-derived exosome injections on the healing of skin wounds. Methods:. A total of 18 Wistar Albino rats were included and randomly allocated into 2 groups. The first group underwent a scalpel incision on the ventral hand surface without any additional treatment. The second group received an identical incision, followed by injections of plant-based exosomes at the wound site. Tissue samples were collected at baseline, as well as on days 7 and 14, for histological assessment of wound healing. Hematoxylin and eosin and Masson trichrome staining were used to evaluate epithelial thickness, collagen deposition, and inflammatory cell infiltration. Results:. The group receiving exosome injections exhibited a significantly enhanced wound healing response compared with the control group. Histological analysis revealed an increase in epithelial thickness, reduced inflammatory cell count, and greater collagen deposition with a more organized structural arrangement, indicating accelerated tissue repair. By day 14, wounds treated with exosomes demonstrated a well-formed epithelium and a substantial reduction in inflammation, highlighting the therapeutic potential of plant-derived exosomes in modulating wound healing dynamics. Conclusions:. The administration of plant-based exosomes into skin wounds resulted in a notable improvement in the healing process. These findings suggest that exosome therapy may enhance tissue regeneration and expedite recovery, making it a promising approach for optimizing wound management and repair. Further research is warranted to explore its broader clinical applications.